D-News & Co / Mohamed Daniel Mohamed Zaini, Nik Aiman Nik Muhamad, Munirah Mustapha…[et.al] - Nik Muhamad, Nik Aiman; Mustapha, Munirah; Amri Lim, Jumaiiyah (MEDEC, 2005)
The Business development in Malaysia is very promising and this gives us opportunity to run a business as well. Our business is mainly about selling goods to people. With the name D-News & Co, people can tell that out main goods are newspapers. Besides newspapers we also provide goods like stationeries and candies. We also provide Photostat and binding services. We are sure that our business will bring us lots of profits because newspapers and the services are a_ daily needs especially for the students and lecturers. Our shop will be located inside the Section 17 campus near the bus parking lot. , We chose this place because it is in the middle of the faculty of accountancy and the faculty of education plus INTEC. As we all know it is next to the bus parking lot. So the students who are in the bus will see our shop first as they step out. Students will also have to gather here for the bus. From there the shop can attract customers. Students are our main target is to earn profit. The UiTM Section 17 Cooperation and Printing Enterprise are our rivals in this business. We have listed down their abilities and weakness. We have to serve better man mem to make sure we are the student's main choice. We hope that this business can survive all the way and not only survive but achieve successfully.